2019
DOI: 10.1186/s13104-019-4409-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of a Rhododendron tomentosum extract does not affect mercury tissue concentrations and excretion rate in methylmercury-treated adult male rats

Abstract: Objectives Consumption of fish/seafood is clearly linked to higher mercury levels in human tissue samples. However, correlations between methylmercury (MeHg) intakes calculated from dietary surveys and mercury body burdens are usually weak and can vary across populations. Different factors may affect MeHg absorption, distribution, metabolism and excretion, including co-exposures to phytochemicals and antibiotics, which were shown to affect mercury body burdens in rodents. Based on the observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The blood levels of mercury above 100 ng/ml were diagnosed with poisoning ( Kamensky et al, 2019 ). After 28 days of exposure to methylmercury, the blood mercury concentration was 76.4 μg/ml, without apparent toxicity observed in rats ( Pelletier et al, 2019 ). Although AGNHP significantly increased blood mercury exposure, it was proved safe by the limited blood mercury exposure at clinical doses.…”
Section: Resultsmentioning
confidence: 99%
“…The blood levels of mercury above 100 ng/ml were diagnosed with poisoning ( Kamensky et al, 2019 ). After 28 days of exposure to methylmercury, the blood mercury concentration was 76.4 μg/ml, without apparent toxicity observed in rats ( Pelletier et al, 2019 ). Although AGNHP significantly increased blood mercury exposure, it was proved safe by the limited blood mercury exposure at clinical doses.…”
Section: Resultsmentioning
confidence: 99%
“…Fish is the major source of mercury; consuming such mercury stored in fish leads to exposure of human tissues to high mercury levels. Pelletier et al [55] examined by checking mercury levels in rodents as they are exposed frequently with Rhododendron tomentosum extract and their blood is with higher mercury levels. Williams et al [56] reported flurbiprofen (anti-inflammatory drug) is the cause of bone resorption disease.…”
Section: Liver-related Effects Due To Mercury Poisoningmentioning
confidence: 99%